In silico Study on Physicochemical, Pharmacokinetic and Toxicity Profiles of Available Antiviral Drugs and The Drug-Target Interaction with Protease of SARS-CoV-2 - Diyah, Nuzul Wahyuning; Ghifari, Aileen Syifa; Hidayati, Shabrina Wahyu; Ekowati, Juni (Camellia : Clinical, Pharmaceutical, Analytical and Pharmacy Community Journal, 2022)
Introduction: In emergency conditions such as the COVID-19 pandemic, many drugs treating SARS-CoV-2 are currently being developed through the concept of repurposing the existing drugs. This study aims to evaluate the physicochemical, pharmacokinetic and toxicity (ADMET) profiles of 15 drugs that have been used clinically for other viral diseases, and inspect their activity as antivirals against SARS-CoV-2. Methods: The physicochemical properties were obtained by using the ChemDraw and the ADMET were predicted using pkCSM on line tools. The selected drugs based on Lipinski's Rules were docked into main protease of SARS-CoV-2 (PDB. 6LU7) using Molegro program. Results: Six drugs complied with Lipinski's Rules and showed good ADMET profile except for their hepatotoxicity, but favipiravir and oseltamivir were predicted to be non-hepatotoxic. Oseltamivir also showed high binding affinity with free energy score below -100 kcal/mol. Conclusions: Oseltamivir is a potential antivirus for COVID-19 based on physicochemical, ADMET profile, and in silico activity against protease of SARS-CoV-2.